UPAYA MENINGKATKAN KETERAMPILAN GERAK LOKOMOTOR ANAK USIA DINI MELALUI PERMAINAN TRADISIONAL ENGKLEK - Isep Djuanda; Rahmi Latifa Suryani (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2021)
The study aims to find out the implementation of traditional game engklek on young learners and to investigate whether young learner’s locomotor movement can improve through traditional game engklek. This study employed action classroom research. The subject of the study is the A group students aged 4-5 years in TK Al-Khawarizmi Depok with the object of the study was the improvement of locomotor movement on children with disabilities by adopting traditional game engklek. The process of the study was conducted in two cycles which preceded by pre-cycles activity. Every cycle consisted of some activities: plan, act, observation, and reflection. The data collection was gathered from observation, interview, and documentation study. The study showed that: 1) the implementation of traditional game engklek could improve locomotor movement skill on young learners aged 4-5 in TK Al-Khawarizmi Depok, indicated by the increasing of the average score in all indicators, including hopping to different direction, jumping to different direction, running and jumping, hopping and turning around, with the precycle result 35,4%, first cycle 56,3%, and second cycle 81,9%; 2) the implementation of traditional game engklek could improve the locomotor movement skill on young learners aged 4-5 in TK Al-Khawarizmi Depok. This was indicated by the result which exceeded the predetermined success criteria.